Analyses of Effective factors on Intensifying of Tourism Space Commodification Process (Case Study: Rural areas of ahmoudabad Town) - Abdolreza Rahmani Fazli; Zhilla Sajjadi; Saber Sedighi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2019)
The present study analyzes the factors affecting the commodification of rural space in Mahmoudabad county of Mazandaran province. In this study, the descriptive-analytical method was used. The statistical population of the study consisted of 91 villages in Mahmoudabad County according to the Census of Iran in 2016. Half of the villages were selected randomly. Data collection was done using a researcher-made questionnaire and processing of satellite images in four periods. The validity of the research instrument was evaluated by the opinion of the relevant professors and experts and its reliability was determined by internal consistency using Cronbach's alpha which ranged from 0.76 to 0.94 for various variables indicating the optimality of the questionnaire. SPSS 22 software was used for data analysis. The tests used in this study were frequency test, single sample t-test, and chi-square test. The results show that the weakness of the tax system (withholding tax on vacant and second homes for tourism, withholding tax on profits from the sale of land and housing), the inefficiency of the banking system (high-interest rates), the weakness of government policies to support the manufacturing sector have made the Mahmoudabad tourism environment fragile. The consequences can be drastic changes in land use, expansion of construction and landscape destruction.